The effect of biological and mineral fertilizers on productivity of spring wheat - M. F. Amirov; L. G. Sagitov; R. N. Salavatullin (Зерновое хозяйство России, 2018)
Both the increase of the crop productivity and the decrease of net costs of its production require necessity to determine and assess the efficiency of each technological method, including a use of expensive mineral fertilizers. The research has been carried out on grey forestry soils with the use of microbiological fertilizers during pre-sowing treatment of the spring soft wheat variety ‘Margarita’. In 2013-2015 the seeds treated with the drugs ‘Mizorin’ and ‘Rizoagrin’ were sown with the use of fertilizers and without them on the experimental fields of FSBEI HE ‘Kazan State Agricultural University’. The use of 170 kg of fertilizers per hectare increased the crop productivity on 510-540 kg/ha. The application of one kg of fertilizers produced 3.0 kg of grain, with the use of ‘Mizorin’ it was 3.64 kg and with the use of ‘Rizoagrin’ it produced 3.76 kg of grain.